1999
DOI: 10.1152/ajplung.1999.277.3.l479
|View full text |Cite
|
Sign up to set email alerts
|

MAPK superfamily activation in human airway smooth muscle: mitogenesis requires prolonged p42/p44 activation

Abstract: Asthma is frequently associated with abnormal airway smooth muscle (ASM) growth that may contribute to airway narrowing and hyperresponsiveness to contractile agents. Although numerous hormones and cytokines have been shown to induce human ASM (HASM) proliferation, the cellular and molecular mechanisms underlying HASM hyperplasia are largely unknown. Here we characterize the roles of the mitogen-activated protein kinase (MAPK) superfamily [p42/p44 MAPK, c-Jun amino-terminal kinase/stress-activated protein kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
120
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(139 citation statements)
references
References 33 publications
17
120
2
Order By: Relevance
“…ASMC proliferation in response to known mitogens such as PDGF and EGF is dependent on activation of the p42/p44 MAPK (17). Results from other studies indicate that the regulation of cytokine-mediated cytokine release also involves the MAPKs.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…ASMC proliferation in response to known mitogens such as PDGF and EGF is dependent on activation of the p42/p44 MAPK (17). Results from other studies indicate that the regulation of cytokine-mediated cytokine release also involves the MAPKs.…”
Section: Discussionmentioning
confidence: 96%
“…The studies with SB-203580 were conducted in duplicate and following 30-min incubation with SB-203580 or serum-free medium, cells were stimulated with 10% human serum for 15 min. Cells were lysed and analyzed by Western blotting using specific monoclonal antibodies against p38 and phospho-p38 (Thr 180 /Tyr 182 ) performed as previously described (17).…”
Section: Phosphorylation Of P38 Mapkmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, our laboratory determined that the signal transducers and activators of transcription (STAT) kinases, Jak and Src, are required for mitogen-induced signaling in human airway smooth muscle cells (HASMC) in vitro (43). Work done by others has demonstrated that the MAPK and PI3-kinase pathways, as well as Rac1, are also important in smooth muscle cell mitogenesis (31,32,35).…”
mentioning
confidence: 99%